Experimental And Numerical Investigations On The Performance Of Flexible Skin Flapping Wing For Micro Aerial Vehicle Application - Yusoff, Hamid (2013)

(untitled)
Flapping-wing micro air vehicles are small, hand-held flying vehicles that can maneuver in a constrained space because of its lightweight, low aspect ratio, and ability to fly in low Reynolds number environment. Flying mammals such as bats, and flying squirrels share a unique feature that allows them to fly with amazing agility and maneuverability unmatched by other flying animals of the same size. The unique feature that allows these animals to have such fight capabilities is their thin and flexible membrane wings. In this work, the unique characteristic features of flexible membrane wings associated with flying mammals such as bats are investigated for their highly efficient aerodynamic abilities. The primary goal of this study is to incorporate the mechanism involved in these flying mammals for improved aerodynamic performance of MAV’s. An Electronic Control System (ECS) was introduced to control a proper flapper wing mechanism to emulate the wing flapping of bats for the ongoing micro air vehicle (MAV) research. Besides, aerodynamic tests were carried out in an open-air wind chamber to investigate the aerodynamic characteristics, particularly the wing skin flexibility and camber effect. Furthermore, the optimization using response surface methodology (RSM) was carried out to investigate the interactive relationship of each factor and optimize the aerodynamic performance. In addition to this, three-dimensional numerical simulation was also accomplished on flat and camber wing using FLUENT software. UDFs were written to mimic the harmonic motion of the flapping wing and the dynamic mesh model was utilized. The aerodynamic performance based on lift and drag coefficient were investigated as functions of AoA, frequency, and velocity. Advance ratio parameter was adopted to study the effects of unsteady flow for flexible and camber wing. The proposed ECS demonstrates efficient control and accurate measurement. Moreover, the tedious procedure involved in the repeated calibrations for the manual system was totally eliminated by ECS. It was found that the most flexible wing skin was best suited for unsteady state with low advance ratio, whereas the least flexible wing was preferred for higher ranges. Furthermore, the experimental results showed that the cambered wings have significantly higher lift and drag when compared to that observed in case of flat wings. Moreover, the optimum result for the aerodynamic performance of the flapping wing characterized based on optimum camber, velocity, and frequency was found to be 15%, 4.29 m/s, and 9 Hz respectively. The numerical results were in good agreement with the experimental findings. The numerical results confirmed the enhancement of aerodynamic performance and camber wing was able to increase by as much as 1.12 times when compared to the flat wing. Investigation on the formation of vortices as well as its strength revealed that a higher camber wing was able to generate a higher LEV strength, provided the shape of the vorticity pattern was more compact, more attached, and more concentrated.